The experience of relatives using intensive care diaries: A systematic review and qualitative synthesis. (July 2021) - Schofield, Rachel; Dibb, Bridget; Coles-Gale, Rebecca; Jones, Christina J
Abstract: Background: Intensive care patient diaries written by staff and/or relatives are widely used in intensive care units (ICUs) across the world. Although the original aim of the diaries was to support patients in their recovery from ICU, a more recent focus of the literature has been the potential benefit of the diaries to the relatives of patients. Meta-analyzes of quantitative studies looking at the impact on the psychological wellbeing of relatives have not consistently found an effect of the diaries, even though qualitative studies suggest that relatives find the diaries to be a useful coping strategy. Objectives: To evaluate and synthesise qualitative studies looking at the experience of relatives writing in ICU diaries. Design: A systematic review and qualitative synthesis. Data sources: A structured search using CINAHL, MEDLINE, PsycInfo, Cochrane Central Register of Controlled Trials (CENTRAL), PTSDHubs and Published International Literature Web of Science Conference Proceedings Citation Index - Science and Social Science and Humanities was conducted. Review methods: All studies published at any time that included qualitative data (including mixed methods studies) about the perceptions of relatives using ICU patient diaries were included. Themes and narrative statements were extracted from included articles and synthesised. Articles were quality assessed using the Critical Appraisal Skills Programme (CASP) qualitative checklist and Mixed Methods Appraisal Tool (MMAT). Results: Sixteen studies were included in the review, thirteen qualitative and three mixed methods articles. The themes identified were: 1. Coping (subthemes: 1.1. Emotion-Focused Coping and 1.2. Problem-Focused Coping) 2. Connection (subthemes: 2.1 Method of Communication and 2.2 Developing and maintaining relationships) 3. Developing a Narrative (subthemes 3.1 Understanding 3.2 Shaping the story 3.3 Remembering). Conclusions: Relatives use the diaries in a variety of ways including as a means of coping, a way of staying connected, as a tool to understand and develop a narrative about the experience. These findings link the use of ICU diaries with literature on written emotional exposure, post-traumatic growth and meaning making. The relationship between a relative's use of the ICU diary, coping strategies and/or post-traumatic growth could be a focus for future quantitative trials. PROSPERO protocol number CRD42020165869